Monitoring, surveillance, antimicrobial resistance and genetic diversity analysis of non-typhoidal Salmonella in South Africa from 1960-2023 from animal and animal products. - Itumeleng Matle; Davies Mubika Pfukenyi; Nozipho Maphori; Nkagiseng Moatshe; Thabo Nkabinde; Annah Motaung; Tracy Schmidt; Emmanuel Seakamela; Mulunda Mwanza; Lubanza Ngoma; Mohamed Sirdar; Khanyisile R Mbatha; et al. (PLoS ONE)
Salmonellosis remains one of the most frequently reported foodborne diseases globally, with the highest burden in low-resource areas. The millions of deaths caused by Nontyphoidal Salmonella (NTS) infections emphasize the urgent need for timely, detailed, and evidence-based interventions to effectively manage and monitor NTS burdens. This study retrospectively analyzed 1,028 NTS isolates from animals, the environment, and food products in South Africa, collected between 1960 and 2023. Among the 102 serotypes identified, S. Heidelberg, isolated only between 2000-2009 and 2020-2023, accounted for 94.3% of isolations during the latter period, suggesting a recent shift in Salmonella epidemiology in the region. The highest resistance rates were observed for cefoxitin (65.7%), cephalothin (62.8%), and tetracycline (59.8%), with a significant increase in resistance to several antibiotics, including ceftriaxone and aztreonam, from 2010-2023. Genetic analysis revealed that S. Gallinarium had the highest prevalence of antibiotic resistance genes, such as tetA (71.4%), qnrA (64.3%), cat1 (64.3%), blaPSE (57.1%), and both blaCMY-2 and qnrB at 50%. The blaPSE and blaSHV genes were strongly associated with ceftriaxone resistance in S. Dublin isolates, while blaPSE and qnrS were linked to chloramphenicol resistance in S. Enteritidis and S. Dublin isolates. Additionally, 87% of the virulence genes screened were present in over 50% of the serotypes, indicating increased adaptability and potential shifts in disease dynamics. The rise in antimicrobial resistance, driven by antimicrobial misuse, horizontal gene transfer, and biofilm formation, could alter serotype dynamics and changing disease epidemiology. This trend underscores the urgent need for effective antimicrobial stewardship and surveillance to combat the spread of antibiotic resistance in Salmonella populations.